Floral diversity in the wetlands of apete river, eleyele lake and oba dam in Ibadan, Nigeria: its implication for biodiversity erosion (2011)
Wetlands in Nigeria face constant threat of destruction by urbanization, road construction and agricultural activities, but the floristic compositions of these fragmented communities are unknown. A comparative assessment study of the floral of three wetlands in a forest-savanna transition ecological zone, Ibadan (70261 N, 30541 E), Oyo State, Nigeria was conducted in the dry and wet seasons of 2002 to assess their species richness, density, community structure and diversity. Thirty-eight plant species from 19 families were enumerated in the three wetlands in two seasons. Nineteen species from 13 families were enumerated in the dry season, while 14 species belonging to nine families were enumerated in the wet season. Eight families were common to both seasons. Eleyele and Apete wetlands had relatively stable flora for both seasons, while Oba dam exhibited pronounced shift in flora between the dry and wet seasons. Continuous perturbation of the three wetlands encouraged proliferation and dominance of some invasive species at the expense of indigenous species populations, leading to subtle biodiversity erosion